Design of a new spray-type seawater evaporator - Kalogirou, Soteris A. (My University, 2001)
The objective of this work is to design a low-cost evaporator. The new type of evaporator suggested here is of the spray-type, i.e., spaying the seawater into fine droplets to evaporate the water. The cost of this type of evaporator is comparatively low because no heat exchangers are required. The evaporator is designed based on the theory of cooling towers. The system is modeled and optimized using heat and mass transfer relations. With proper design the spray-mode of evaporation is superior to both pool boiling and thin-film evaporation. It is shown that the rate of evaporation is mainly influenced from the droplet size and temperature, i.e., the evaporation is enhanced by having small-diameter and high-temperature water droplets. A limitation of the suggested system is that either good filtration equipment needs to be used or the droplet size could not be low enough. Also it is desirable not to operate the systems with temperatures higher than 70°C, a temperature that can easily be obtained with comparatively cheap flat-plate solar collectors. Typical expected results are presented which prove the viability of the proposed system. The complete system consisting of the evaporator, a solar collector 1 m2 in area and pumps is modeled with TRNSYS. Such a system gives 11.2m3/y of fresh water.
Keywords: Spray evaporator; Design; Modeling; TRNSYS program